Speak and Shine: “Talk Dice Game” for Young English Learners - Nussy, Wenssy Steva; Tiven, Punggulina Andawaty; Suryaningrum, Sumarah; Oraile, Orpa Penina; Ngosiem, Maria Jomima; Lorang, Liviya Donice (Abdimas Indonesian Journal, 2025)
The aim of this community service project is to investigate the implementation of the "Talk Dice Game" to improve the students' vocabulary skill in sentence construction in the fifth grade students of SD Kristen 1 Dobo which amounted to 28 students (Class VA). Although animals and body parts were previously introduced in English, students’ lexical knowledge was extended to four new categories: hobbies, food, family and jobs. Students played a game in which they rolled three dices to get a topic, a sentence starter, and the style of speaking; and then they each had to read the sentence they created in the style indicated by the third dice. The game promoted the technique of thinking on-the-spot, and also, created some rather surprising sentences. The findings were that not only did the game serve to promote vocabulary retention, it also enabled students to experiment with sentence-construction even with minimal training in grammar. The game supports the value of gamified, scaffolded language learning methods to early English instruction in an Indonesian primary school.